The Representation of Linguistics in Simbolic Figth of Commercial Advertising Discourse - Jufri, Jufri; Tolla, Achmad (Indonesian Journal of Educational Studies, 2014)
This study aimed to describe the linguistic entity empowered to fight symbolic discourse komersia advertising in mass medai. Designed qualitative research. Data were collected by document analysts techniques. Data were analyzed with flow models Miles and Huberman. The results showed that the advertising discourse laden with a cargo of ideology and power. Being empowered linguistic comprising: vocabulary, modalities, numbers, pronouns, phrases, clauses, and sentences